Financial dollarization: The role of foreign-owned banks and interest rates - Basso, Henrique S.; Calvo-Gonzalez, Oscar; Jurgilas, Marius (Journal of Banking & Finance, 2011)
Why in many economies households and firms borrow and make deposits in foreign currency? Expanding on the existing literature, our framework addresses this question allowing for interest rate differentials and access to foreign funds to play a role in explaining this process of asset substitution or financial dollarization. Using a newly compiled data set on transition economies and employing a standard panel as well as a panel-VAR methodology we find that increasing access to foreign funds leads to higher credit dollarization, while it decreases deposit dollarization. Interest rate differentials matter for the dollarization of both loans and deposits.